2014
DOI: 10.1103/physrevx.4.021044
|View full text |Cite
|
Sign up to set email alerts
|

Robust Two-Qubit Gates for Donors in Silicon Controlled by Hyperfine Interactions

Abstract: We present two strategies for performing two-qubit operations on the electron spins of an exchange-coupled pair of donors in silicon, using the ability to set the donor nuclear spins in arbitrary states. The effective magnetic detuning of the two electron qubits is provided by the hyperfine interaction when the two nuclei are prepared in opposite spin states. This can be exploited to switch on and off SWAP operations with modest tuning of the electron exchange interaction. Furthermore, the hyperfine detuning e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
98
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 53 publications
1
98
1
Order By: Relevance
“…A splitting of 6 MHz could either be caused by a hyperfine-coupled 29 Si on the nearest-neighbor site, 25 or by another 31 P donor, coupled to the donor under measurement by an exchange interaction J ¼ 14 MHz, assuming that the two-electron system is initialized in the j ##i state. 26 An exchange coupling of this magnitude corresponds to an inter-donor separation of $20 nm 27 and is compatible with the expected inter-donor distance from 20 keV P þ 2 molecular implantation. The donor under study is found predominantly in the nuclear j+i state, but other ESR spectra in the nuclear j*i state (data not shown) allowed us to determine the value of the hyperfine coupling A HF ¼ 114.4 MHz.…”
supporting
confidence: 65%
“…A splitting of 6 MHz could either be caused by a hyperfine-coupled 29 Si on the nearest-neighbor site, 25 or by another 31 P donor, coupled to the donor under measurement by an exchange interaction J ¼ 14 MHz, assuming that the two-electron system is initialized in the j ##i state. 26 An exchange coupling of this magnitude corresponds to an inter-donor separation of $20 nm 27 and is compatible with the expected inter-donor distance from 20 keV P þ 2 molecular implantation. The donor under study is found predominantly in the nuclear j+i state, but other ESR spectra in the nuclear j*i state (data not shown) allowed us to determine the value of the hyperfine coupling A HF ¼ 114.4 MHz.…”
supporting
confidence: 65%
“…This design can also benefit from improved addressability 2 and longer T 1 times, 3 and can be used in conjunction with the two-qubit scheme proposed in ref. 11. This design can therefore overcome some of the experimental obstacles for realising a two-qubit gate in silicon.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, scalable architectures have been proposed to extend single qubit control techniques to larger structures [12,13].…”
Section: Introductionmentioning
confidence: 99%